A light-curing acrylic adhesive for PVD process protection and preparation method thereof
By modifying acrylic resin and photocuring acrylic adhesive with modified silica and activated graphene, the problems of special-shaped structure bonding and peeling under high temperature conditions during PVD are solved, and the protection effect of high precision and low adhesion is achieved. Suitable for large-scale applications.
Patent Information
- Application Number
- CN202411288923.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing PVD process protection materials are difficult to fully fit the special-shaped structure under high temperature conditions, resulting in low plating accuracy, curling and over-plating, and difficulty in peeling the entire body, limiting the technical update of engineering design.
Photocured acrylic adhesives with modified acrylic resins, modified silica and activated graphene are used to improve their high temperature resistance, low adhesion and bonding properties through specific preparation methods and combination formulas, ensuring that they do not rise at high temperatures. And easy to peel off as a whole.
It realizes close fit and high-precision protection of special-shaped structures at high temperatures, reduces deformation and over-plating of the coating, improves the stability and peel strength of the coating, and is suitable for large-scale applications.
Smart Images

Figure CN118813197B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light-curing acrylic adhesives, and in particular to a light-curing acrylic adhesive for PVD process protection and a preparation method thereof, and in particular to a light-curing acrylic adhesive suitable for PVD process protection of metals and plastics and a preparation method thereof. Background Art
[0002] In the field of consumer electronics, physical vapor deposition (PVD) coating is generally used on materials. This is an advanced surface treatment technology that uses physical methods such as evaporation, sputtering or ion plating in a vacuum to deposit a thin film with specific functions on the surface of the workpiece.
[0003] There are many types of PVD coatings, including but not limited to metal films, nitride films, carbide films and oxide films. These films have high hardness, high wear resistance, low friction coefficient, good corrosion resistance and chemical stability, and improve their appearance and decorative properties. PVD coating technology also has environmental advantages because it does not involve the use of harmful chemicals and can obtain micron-level coatings.
[0004] Physical vapor deposition technology can be divided into three process steps:
[0005] (1) Vaporization of the plating material: the plating material is evaporated, sublimated or sputtered, that is, through the vaporization source of the plating material.
[0006] (2) Migration of plating material atoms, molecules or ions: Atoms, molecules or ions supplied by the vaporization source collide and produce various reactions.
[0007] (3) The plating atoms, molecules or ions are deposited on the substrate.
[0008] At present, the PVD process protection materials used in the market are generally plastic plugs or film lamination. The PVD process generally requires a higher temperature, which places increasingly higher requirements on the performance of the protective material, requiring the protective film to not wrinkle and have a small expansion and contraction rate.
[0009] However, existing plastic plugs cannot provide full fit protection. Generally, there is a gap at the junction of the plug and the substrate, resulting in low coating accuracy. At the same time, the plug and the film cannot fully fit the special-shaped structure, which limits the technical updates of engineering designers during design.
[0010] Therefore, how to develop a protective film that has good heat resistance, is easy to peel off, and has no edge warping during high-temperature processes has excellent research prospects. Summary of the invention
[0011] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a light-curing acrylic adhesive for PVD process protection and a preparation method thereof.
[0012] A light-curing acrylic adhesive for PVD process protection comprises the following raw materials by mass: 30-50 parts of modified acrylic resin, 10-30 parts of acrylic monomer, 30-50 parts of modified silicon dioxide, 1-5 parts of free radical initiator and 1-10 parts of surfactant.
[0013] Preferably, the modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are mixed, the temperature is raised to 65-75°C and stirred evenly, a platinum catalyst is added, the vacuum state is adjusted and stirred for 3.5-4.5 hours to obtain a hydroxyl-terminated polybutadiene and a side group-containing comb-type siloxane prepolymer 1; then diphenylmethane diisocyanate is added, the vacuum state is maintained and stirred for 40-80 minutes, and an isocyanate prepolymer 2 with NCO end-capped at both ends is obtained; then methacrylate-2-hydroxyethyl ester monomer is added, the vacuum state is maintained and stirred for 40-80 minutes, and a modified acrylic acid with acrylic acid end-capped at both ends is obtained.
[0014] The structure of prepolymer is as follows:
[0015]
[0016] The structure of prepolymer II is as follows:
[0017]
[0018] The structure of modified acrylic resin is as follows:
[0019]
[0020] More preferably, the molar ratio of the hydroxyl-terminated polybutadiene to the monohydrogen silicone oil is 3-3.2:1.
[0021] More preferably, the sum of the masses of the hydroxyl-terminated polybutadiene, the monohydrogen silicone oil and the platinum catalyst is m , the mass of the platinum catalyst is n ,but n / m =3-5: 1000000.
[0022] More preferably, the molar ratio of isocyanate groups in diphenylmethane diisocyanate to hydroxyl groups in prepolymer 1 is 2-2.2:1.
[0023] More preferably, the molar ratio of the hydroxyl groups in the 2-hydroxyethyl methacrylate monomer to the isocyanate groups in the prepolymer is 1-1.1:1.
[0024] More preferably, the vacuum degree of the vacuum state is -80 to -100 kPa.
[0025] Preferably, the acrylic monomer is at least one of isooctyl acrylate, isodecyl acrylate, isobutyl acrylate, isopropyl acrylate, dodecyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, acryloylmorpholine, and isobornyl acrylate.
[0026] Preferably, the particle size of the modified silica is <10 μm.
[0027] Preferably, the modified silica is ultrafine acrylate system modified silica.
[0028] Preferably, the modified silica is methacrylic acid modified silica.
[0029] Preferably, methacrylic acid modified silica is prepared by the following specific operation: adding nano-silica to deionized water for ultrasonic dispersion for 20-60 minutes, then adding methacrylic acid and initiator, polymerizing at 80-90° C. for 1-2 hours, cooling to room temperature, vacuum drying, and crushing.
[0030] More preferably, the mass ratio of nano-silicon dioxide, methacrylic acid and initiator is 80-120:2-4:0.01-0.05.
[0031] Preferably, methacrylic acid modified silica is prepared by the following specific operation: adding activated silica, methacrylic acid and butyl acrylate into water and stirring evenly, adding initiator, polymerizing at 80-90° C. for 1-2 hours, cooling to room temperature, vacuum drying and crushing.
[0032] More preferably, the mass ratio of activated silica, methacrylic acid, butyl acrylate and initiator is 5-15:1-3:1-2:0.01-0.1.
[0033] More preferably, the initiator is potassium persulfate or sodium persulfate.
[0034] More preferably, the activated silica is prepared by the following specific operation: dopamine and tetraethyl orthosilicate are added to ethyl acetate and stirred evenly to obtain a prefabricated material; Tris-HCl solution with a pH value of 8-9 is added dropwise to the prefabricated material at a temperature of 50-60°C and stirred for 1-3 minutes, cooled to 30-36°C, the pH value of the system is adjusted to 6-6.5, stirring is continued for 5-20 minutes, filtered, washed, vacuum dried, calcined at 500-600°C to obtain porous microspheres, which are then dispersed in an ethanol aqueous solution and stirred evenly, an aminosilane coupling agent is added and ultrasonically treated for 1-2 hours, filtered, and vacuum dried.
[0035] The invention adopts dopamine and tetraethyl orthosilicate to compound, add them into ethyl acetate to form an oil phase, form oil-in-water droplets under high-speed stirring, self-polymerize dopamine to form a small ball structure, and deposit tetraethyl orthosilicate on the surface of the small ball structure. The obtained composite microspheres are calcined to form a porous microsphere structure, and activated silicon dioxide is formed on the surface of the small ball structure.
[0036] The activated silica obtained is combined with methacrylic acid and butyl acrylate monomers to obtain methacrylic acid modified silica. Then it is compounded with modified acrylic resin, which not only has good mutual affinity and extremely high mutual dispersion, but also has microspheres that deform during pressing, so that the system is in full contact with the surface of the workpiece being adhered, and has excellent special-shaped structure bonding effect; and because of the special microsphere structure of modified silica, it can also support the acrylic adhesive and the workpiece being adhered, so that the peeling strength of the acrylic adhesive can be stably maintained, avoiding over-adhesion or non-adhesion, and achieving good peeling effect.
[0037] More preferably, the mass ratio of dopamine, tetraethyl orthosilicate and aminosilane coupling agent is 1-3:1-5:0.1-1.
[0038] More preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane or 3-(2-aminoethylamino)propyltrimethoxysilane.
[0039] Preferably, the surfactant is a Span series or a Tween series.
[0040] Preferably, the free radical initiator is at least one of photoinitiator 184, photoinitiator TPO, photoinitiator TMO, photoinitiator ITX, IGM 907, and IGM 320.
[0041] Preferably, the raw materials also include: activated graphene, and the mass ratio of activated graphene to modified silicon dioxide is 1-3:30-50. The activated graphene is prepared by the following specific operation: adding hexadecyltrimethylammonium bromide and graphene oxide to deionized water, stirring at 50-70°C for 1-2h, filtering, washing, and vacuum drying.
[0042] The present invention adopts activated graphene as a raw material. Due to the sheet structure of graphene oxide combined with the long carbon chain structure of hexadecyltrimethylammonium bromide bonded thereto, it can not only combine with monomers that have not yet reacted in the raw material to significantly reduce the thermal shrinkage rate, but also cooperate with the modified silicon dioxide to make the product fit tightly with the special-shaped structure without warping during high temperature, and can also be easily peeled off as a whole under the special-shaped structure, so as to better protect the surface of the workpiece.
[0043] More preferably, the mass ratio of hexadecyltrimethylammonium bromide to graphene oxide is 0.1-1:1-3.
[0044] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0045] a) Stir the modified acrylic resin, acrylic monomer, free radical initiator and surfactant evenly;
[0046] b) then adding modified silicon dioxide and stirring evenly, or, then adding modified silicon dioxide and activated graphene and stirring evenly;
[0047] c) After grinding, stir evenly, heat to 68-72℃, adjust the vacuum degree to -80~-100kPa and maintain for 40-80min.
[0048] Preferably, in step c), grinding is performed using a three-roll mill with a gap of 40 / 10 μm.
[0049] The invention introduces an organic silicon segment into the molecular chain of hydroxy polybutadiene resin to improve the temperature resistance and ensure low adhesion, so that the modified acrylic resin has low adhesion and good temperature resistance; a temperature-resistant monomer with a long molecular chain is used as a diluent, and modified silicon dioxide is added to reduce the shrinkage rate, thereby ensuring the sizing accuracy.
[0050] The present invention has the following technical effects:
[0051] 1. It has excellent high temperature resistance and ultra-low volatility at high temperatures, and can provide excellent special-shaped structure bonding effect through piezoelectric ceramic valve injection or injection molding;
[0052] 2. Its curing shrinkage is ≤0.3%, which can maintain high processing accuracy; its excellent high temperature resistance and low adhesion characteristics, its elongation at break and hardness have no obvious changes after the PVD process, and it is easy to peel off as a whole under special-shaped structures;
[0053] 3. Its ultra-low volatility does not interfere with the adhesion of the coating under high temperature and vacuum conditions, especially in the hole structure;
[0054] 4. Its lower viscosity allows the use of automated equipment for gluing, and its lower adhesion allows the use of automated glue removal, saving a lot of manpower and material resources and improving efficiency;
[0055] 5. The PVD process protective film prepared by the light-curing acrylic adhesive obtained by the present invention not only reduces the deformation of the protective film, controls the expansion and shrinkage rate, and prevents overflow plating during the PVD process, but also has a smaller viscosity increase after the high-temperature process, making it easy to peel off. At the same time, there is no warping at the edge during the high-temperature process, which can effectively protect the surface of the structure and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1The figure is a comparison chart of the curing shrinkage and expansion / contraction ratio of the light-curing acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example.
[0057] Figure 2 The following is a comparison chart of the peel strength of the photocurable acrylic adhesives obtained in Example 3, Example 6, Example 7 and the comparative example before and after the PVD process.
[0058] Figure 3 This is a comparison chart of the peel strength change rate, elongation at break retention rate, and hardness retention rate of the light-curing acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example before and after the PVD process. DETAILED DESCRIPTION
[0059] The present invention will be further explained below in conjunction with specific embodiments.
[0060] Example 1
[0061] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 30g of modified acrylic resin, 7g of isooctyl acrylate, 3g of acryloyl morpholine, 30g of methacrylic acid-modified silica with a particle size of less than 10μm, 0.6g of photoinitiator 184, 0.4g of photoinitiator TPO, and 1g of Span 60.
[0062] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added to a reactor at a molar ratio of 3:1, the temperature in the reactor is heated to 65°C and stirred evenly, and then 3ppm of platinum catalyst is added, the vacuum degree is adjusted to -80kPa, and stirred for 3.5h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2:1, the vacuum degree is maintained at -80kPa, and stirred for 40min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1:1, and the vacuum state is maintained and stirred for 40-80min.
[0063] Methacrylic acid modified silica was prepared by the following specific operation: 80 g of nano-silica was added to 400 g of deionized water and ultrasonically dispersed for 20 min, then 2 g of methacrylic acid and 0.01 g of potassium persulfate were added, polymerized at 80° C. for 1 h, cooled to room temperature, vacuum dried, and crushed.
[0064] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0065] a) Add modified acrylic resin, isooctyl acrylate, acryloyl morpholine, photoinitiator 184, photoinitiator TPO and Span 60 into a planetary stirring kettle and stir evenly;
[0066] b) then add methacrylic acid modified silica and stir evenly;
[0067] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 68°C, adjust the vacuum degree to -80 kPa and maintain for 40 minutes, and then discharge / package.
[0068] Example 2
[0069] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 50g of modified acrylic resin, 20g of isodecyl acrylate, 10g of isobornyl acrylate, 50g of methacrylic acid-modified silica with a particle size of less than 10μm, 75g of IGM 90, and 10g of Tween 60.
[0070] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added to a reactor at a molar ratio of 3.2:1, the temperature in the reactor is heated to 75°C and stirred evenly, and then 5ppm of platinum catalyst is added, the vacuum degree is adjusted to -100kPa, and stirred for 4.5h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.2:1, the vacuum degree is maintained at -100kPa, and stirred for 80min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.1:1, and the vacuum state is maintained and stirred for 80min.
[0071] Methacrylic acid modified silica was prepared by the following specific operation: 120 g of nano-silica was added to 600 g of deionized water and ultrasonically dispersed for 60 min, then 4 g of methacrylic acid and 0.05 g of potassium persulfate were added, polymerized at 90° C. for 2 h, cooled to room temperature, vacuum dried, and crushed.
[0072] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0073] a) Add modified acrylic resin, isodecyl acrylate, isobornyl acrylate, IGM 907 and Tween 60 into a planetary stirred tank and stir evenly;
[0074] b) then add methacrylic acid modified silica and stir evenly;
[0075] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 72°C, adjust the vacuum degree to -100 kPa and maintain for 80 minutes, and then discharge / package.
[0076] Example 3
[0077] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 40g of modified acrylic resin, 6g of isooctyl acrylate, 4g of isopropyl acrylate, 10g of acryloyl morpholine, 40g of methacrylic acid-modified silica with a particle size of less than 10μm, 3g of photoinitiator 184, and 5g of Tween 80.
[0078] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added into a reaction kettle at a molar ratio of 3.1:1, the temperature in the kettle is heated to 70°C and stirred evenly, and then 4ppm of platinum catalyst is added, the vacuum degree is adjusted to -90kPa, and stirred for 240h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.1:1, the vacuum degree is maintained at -90kPa, and stirred for 60min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.05:1, and the vacuum state is maintained and stirred for 60min.
[0079] Methacrylic acid modified silica was prepared by the following specific operation: 100 g of nano-silica was added to 500 g of deionized water and ultrasonically dispersed for 40 min, then 3 g of methacrylic acid and 0.03 g of potassium persulfate were added, polymerized at 85° C. for 1.5 h, cooled to room temperature, vacuum dried, and crushed.
[0080] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0081] a) Add modified acrylic resin, isooctyl acrylate, isopropyl acrylate, acryloylmorpholine, photoinitiator 184 and Tween 80 into a planetary stirring tank and stir evenly;
[0082] b) then add methacrylic acid modified silica and stir evenly;
[0083] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -90 kPa and maintain for 60 minutes, then discharge / package.
[0084] Example 4
[0085] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 35g of modified acrylic resin, 25g of isopropyl acrylate, 35g of methacrylic acid-modified silica with a particle size of less than 10μm, 1.5g of photoinitiator TMO, 2.5g of IGM 320, and 2g of Tween 80.
[0086] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added to a reactor at a molar ratio of 3.15:1, the temperature in the reactor is heated to 68°C and stirred evenly, and then 4.5ppm of platinum catalyst is added, the vacuum degree is adjusted to -85kPa, and stirred for 260h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.05:1, the vacuum degree is maintained at -95kPa, and stirred for 50min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.08:1, and the vacuum state is maintained and stirred for 50min.
[0087] Methacrylic acid modified silica was prepared by the following specific operation: 15 g activated silica, 1 g methacrylic acid, and 2 g butyl acrylate were added to 20 g water and stirred evenly, 0.1 g potassium persulfate was added, polymerization reaction was carried out at a temperature of 80° C. for 2 h, the temperature was cooled to room temperature, vacuum dried, and crushed.
[0088] The activated silica was prepared by the following specific operation: 1 g dopamine and 5 g ethyl orthosilicate were added to 25 g ethyl acetate and stirred evenly to obtain a prefabricated material; 10 g Tris-HCl solution with a pH of 8 was added dropwise to the prefabricated material at a temperature of 60°C, stirred at a speed of 4000 r / min for 3 min, cooled to 30°C, and the pH value of the system was adjusted to 6 with hydrochloric acid, and stirred for 20 min. The prefabricated material was filtered, washed, vacuum dried, and calcined at a temperature of 500°C to obtain porous microspheres, which were then dispersed in 40 g 40% ethanol aqueous solution and stirred evenly. 1 g 3-aminopropyltriethoxysilane was added, and ultrasonic treatment was performed for 1 h at an ultrasonic frequency of 15 kHz. The prefabricated material was filtered and vacuum dried.
[0089] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0090] a) Add modified acrylic resin, isopropyl acrylate, photoinitiator TMO, IGM 320 and Tween 80 into a planetary stirred tank and stir evenly;
[0091] b) then add methacrylic acid modified silica and stir evenly;
[0092] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -85 kPa and maintain for 70 minutes, and then discharge / package.
[0093] Example 5
[0094] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 45g of modified acrylic resin, 15g of dodecyl acrylate, 45g of methacrylic acid-modified silica with a particle size of less than 10μm, 2g of photoinitiator TPO, and 808g of Span.
[0095] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added into a reaction kettle at a molar ratio of 3.05:1, the temperature in the kettle is heated to 72°C and stirred evenly, and then 3.5ppm of platinum catalyst is added, the vacuum degree is adjusted to -95kPa, and stirred for 220h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.15:1, the vacuum degree is maintained at -85kPa, and stirred for 70min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.02:1, and the vacuum state is maintained and stirred for 70min.
[0096] Methacrylic acid modified silica was prepared by the following specific operation: 5 g activated silica, 3 g methacrylic acid, and 1 g butyl acrylate were added to 40 g water and stirred evenly, 0.01 g potassium persulfate was added, polymerization reaction was carried out at a temperature of 90° C. for 1 h, the temperature was cooled to room temperature, vacuum dried, and crushed.
[0097] The activated silica was prepared by the following specific operation: 3 g dopamine and 1 g tetraethyl orthosilicate were added to 50 g ethyl acetate and stirred evenly to obtain a prefabricated material; 5 g Tris-HCl solution with a pH of 9 was added dropwise to the prefabricated material at a temperature of 50°C, stirred at a speed of 6000 r / min for 1 min, cooled to 36°C, and the pH value of the system was adjusted to 6.5 with hydrochloric acid, and stirred for 5 min. The microspheres were filtered, washed, vacuum dried, and calcined at a temperature of 600°C to obtain porous microspheres, which were then dispersed in 20 g of a 60% ethanol aqueous solution and stirred evenly. 0.1 g 3-(2-aminoethylamino)propyltrimethoxysilane was added, and ultrasonic treatment was performed for 2 h at an ultrasonic frequency of 5 kHz. The microspheres were filtered and vacuum dried.
[0098] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0099] a) Add modified acrylic resin, dodecyl acrylate, photoinitiator TPO and Span 80 into a planetary stirring kettle and stir evenly;
[0100] b) then add methacrylic acid modified silica and stir evenly;
[0101] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -95 kPa and maintain for 50 minutes, and then discharge / package.
[0102] Example 6
[0103] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 40g of modified acrylic resin, 6g of isooctyl acrylate, 4g of isopropyl acrylate, 10g of acryloyl morpholine, 40g of methacrylic acid-modified silica with a particle size of less than 10μm, 3g of photoinitiator 184, and 5g of Tween 80.
[0104] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added into a reaction kettle at a molar ratio of 3.1:1, the temperature in the kettle is heated to 70°C and stirred evenly, and then 4ppm of platinum catalyst is added, the vacuum degree is adjusted to -90kPa, and stirred for 240h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.1:1, the vacuum degree is maintained at -90kPa, and stirred for 60min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.05:1, and the vacuum state is maintained and stirred for 60min.
[0105] Methacrylic acid modified silica was prepared by the following specific operation: 10 g activated silica, 2 g methacrylic acid, and 1.5 g butyl acrylate were added to 25 g water and stirred evenly, 0.05 g potassium persulfate was added, polymerization reaction was carried out at a temperature of 85° C. for 1.5 h, the temperature was cooled to room temperature, vacuum dried, and crushed.
[0106] The activated silica was prepared by the following specific operation: 2g dopamine and 3g ethyl orthosilicate were added to 35g ethyl acetate and stirred evenly to obtain a prefabricated material; 8g Tris-HCl solution with pH=8.5 was added dropwise to the prefabricated material at a temperature of 55°C, stirred at a speed of 5000r / min for 2min, cooled to 33°C, and the pH value of the system was adjusted to 6.3 with hydrochloric acid, and stirred for 12min, filtered, washed, vacuum dried, and calcined at a temperature of 550°C to obtain porous microspheres, which were then dispersed in 30g of 50% ethanol aqueous solution and stirred evenly, 0.5g 3-aminopropyltriethoxysilane was added, ultrasonically treated for 1.5h with an ultrasonic frequency of 10kHz, filtered, and vacuum dried.
[0107] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0108] a) Add modified acrylic resin, isooctyl acrylate, isopropyl acrylate, acryloylmorpholine, photoinitiator 184 and Tween 80 into a planetary stirring tank and stir evenly;
[0109] b) then add methacrylic acid modified silica and stir evenly;
[0110] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -90 kPa and maintain for 60 minutes, then discharge / package.
[0111] Example 7
[0112] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 40g of modified acrylic resin, 6g of isooctyl acrylate, 4g of isopropyl acrylate, 10g of acryloylmorpholine, 40g of methacrylic acid-modified silicon dioxide with a particle size of less than 10μm, 1-3g of activated graphene, 3g of photoinitiator 184, and 5g of Tween 80.
[0113] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added into a reaction kettle at a molar ratio of 3.1:1, the temperature in the kettle is heated to 70°C and stirred evenly, and then 4ppm of platinum catalyst is added, the vacuum degree is adjusted to -90kPa, and stirred for 240h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.1:1, the vacuum degree is maintained at -90kPa, and stirred for 60min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.05:1, and the vacuum state is maintained and stirred for 60min.
[0114] Methacrylic acid modified silica was prepared by the following specific operation: 10 g activated silica, 2 g methacrylic acid, and 1.5 g butyl acrylate were added to 25 g water and stirred evenly, 0.05 g potassium persulfate was added, polymerization reaction was carried out at a temperature of 85° C. for 1.5 h, the temperature was cooled to room temperature, vacuum dried, and crushed.
[0115] The activated silica was prepared by the following specific operation: 2g dopamine and 3g ethyl orthosilicate were added to 35g ethyl acetate and stirred evenly to obtain a prefabricated material; 8g Tris-HCl solution with pH=8.5 was added dropwise to the prefabricated material at a temperature of 55°C, stirred at a speed of 5000r / min for 2min, cooled to 33°C, and the pH value of the system was adjusted to 6.3 with hydrochloric acid, and stirred for 12min, filtered, washed, vacuum dried, and calcined at a temperature of 550°C to obtain porous microspheres, which were then dispersed in 30g of 50% ethanol aqueous solution and stirred evenly, 0.5g 3-aminopropyltriethoxysilane was added, ultrasonically treated for 1.5h with an ultrasonic frequency of 10kHz, filtered, and vacuum dried.
[0116] The activated graphene was prepared by the following specific operation: 0.5 g of hexadecyltrimethylammonium bromide and 2 g of graphene oxide were added to 15 g of deionized water, stirred at a temperature of 60° C. for 1.5 h, filtered, washed, and vacuum dried.
[0117] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0118] a) Add modified acrylic resin, isooctyl acrylate, isopropyl acrylate, acryloylmorpholine, photoinitiator 184 and Tween 80 into a planetary stirring tank and stir evenly;
[0119] b) then adding modified silica and activated graphene and stirring evenly;
[0120] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -90 kPa and maintain for 60 minutes, then discharge / package.
[0121] Comparative Example
[0122] A light-curing acrylic adhesive for PVD process protection, the raw materials of which include: 40g of modified acrylic resin, 6g of isooctyl acrylate, 4g of isopropyl acrylate, 10g of acryloyl morpholine, 40g of methacrylic acid-modified silica with a particle size of less than 10μm, 3g of photoinitiator 184, and 5g of Tween 80.
[0123] The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are added into a reaction kettle at a molar ratio of 3.1:1, the temperature in the kettle is heated to 70°C and stirred evenly, and then 4ppm of platinum catalyst is added, the vacuum degree is adjusted to -90kPa, and stirred for 240h to obtain prepolymer 1; then diphenylmethane diisocyanate is added at a molar ratio of NCO:OH=2.1:1, the vacuum degree is maintained at -90kPa, and stirred for 60min to obtain prepolymer 2; then, methacrylate-2-hydroxyethyl ester monomer is added after dehydration according to the molar ratio of OH:NCO=1.05:1, and the vacuum state is maintained and stirred for 60min.
[0124] Methacrylic acid modified silica was prepared by the following specific operation: 10 g activated silica, 2 g methacrylic acid, and 1.5 g butyl acrylate were added to 25 g water and stirred evenly, 0.05 g potassium persulfate was added, polymerization reaction was carried out at a temperature of 85° C. for 1.5 h, the temperature was cooled to room temperature, vacuum dried, and crushed.
[0125] The activated silica was prepared by the following specific operation: 3 g of tetraethyl orthosilicate was added to 35 g of ethyl acetate and stirred evenly to obtain a preform; 8 g of Tris-HCl solution with a pH of 8.5 was added dropwise to the preform, stirred at a speed of 5000 r / min for 2 min, the pH value of the system was adjusted to 6.3 with hydrochloric acid, and the stirring was continued for 12 min, filtered, washed, and vacuum dried, and then dispersed in 30 g of 50% ethanol aqueous solution and stirred evenly, 0.5 g of 3-aminopropyltriethoxysilane was added, ultrasonic treatment was performed for 1.5 h, the ultrasonic frequency was 10 kHz, filtered, and vacuum dried.
[0126] The method for preparing the light-curing acrylic adhesive for PVD process protection comprises the following steps:
[0127] a) Add modified acrylic resin, isooctyl acrylate, isopropyl acrylate, acryloylmorpholine, photoinitiator 184 and Tween 80 into a planetary stirring tank and stir evenly;
[0128] b) then add methacrylic acid modified silica and stir evenly;
[0129] c) Grind with a three-roll mill (gap of 40 / 10 μm), then send into a planetary stirring kettle for uniform mixing, heat to 70°C, adjust the vacuum degree to -90 kPa and maintain for 60 minutes, then discharge / package.
[0130] The photocurable acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example was coated on the surface of the glass substrate with a coating size of 30 mm×5 mm×1 mm and irradiated with UV light (30 mW / cm 2 ) Curing for 120 seconds and calculate the curing shrinkage.
[0131] Curing shrinkage = (volume after coating - volume after curing) ÷ volume after coating × 100%
[0132] Then, the photocurable acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example was coated on the surface of the release film, and the thickness of the acrylic adhesive layer was 6 μm; it was dried at 110°C, and then compounded with the low-precipitation PET film and rolled up. The protective film was placed in a aging chamber and aged at 55°C for 72 hours. The PVD process protective film sample obtained above was punched with a puncher and then attached to the surface of the glass sheet, and the basic data of the circle was calibrated using a two-dimensional image measuring instrument; after the PVD process, the deformation data of the circle was calibrated using a two-dimensional image measuring instrument, and the expansion and contraction rate was calculated.
[0133] Expansion / shrinkage ratio = (radius of sample after PVD process - original radius of sample) ÷ original radius of sample × 100%
[0134] like Figure 1 As shown, the curing shrinkage rate of the light-curing acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example is less than 0.3%, and the expansion and contraction rate is less than 0.25%, which proves that all four can be applied to the protective film of the PVD process. However, the curing shrinkage rate and expansion and contraction rate of the light-curing acrylic adhesive obtained in Example 7 are the lowest, which is better than the other groups (P < 0.05), can maintain higher processing accuracy, can fully fit the special-shaped structure, avoid affecting the PVD coating, and can also avoid wrinkling and edge warping during high temperature processes.
[0135] The light-curable acrylic adhesive obtained in Example 3, Example 6, Example 7 and the comparative example was coated on the surface of the release film, and the thickness of the acrylic adhesive layer was 6 μm; it was dried at 110° C., and then compounded with the low-precipitation PET film and rolled up. The protective film was placed in a curing chamber at 55° C. for 72 hours.
[0136] The elongation at break and hardness of the PVD process protective film sample obtained above were measured. The PVD process protective film sample obtained above was applied to the surface of a glass substrate to test its peel strength (refer to GB / T 2792-2014 "Test method for peel strength of adhesive tape").
[0137] Then, after the PVD process, the peel strength is tested again, and the elongation at break and hardness are tested again, and the change rate of the elongation at break and the hardness is calculated.
[0138] Retention rate of elongation at break / hardness = elongation at break and hardness after PVD process ÷ original elongation at break / hardness × 100%
[0139] Change rate of peel strength before and after PVD process = (peel strength after PVD process - peel strength before PVD process) ÷ peel strength before PVD process × 100%
[0140] like Figure 2 As shown, although the peel strength of the photocurable acrylic adhesive obtained in Example 7 before and after the PVD process is the highest, it is still lower than 1N / cm, and its viscosity increase is small.
[0141] The peel strength change rate before and after the PVD process was calculated, and it was found that the peel strength change rate of the photocurable acrylic adhesive obtained in Example 7 was the smallest, indicating that the peel strength of the photocurable acrylic adhesive obtained in Example 7 can be stably maintained to avoid over-stickiness or non-stickiness, resulting in a good peeling effect.
[0142] like Figure 3 As shown, in the light-curing acrylic adhesive obtained in Example 7, the changes in peel strength, elongation at break and hardness are extremely small, which is conducive to the overall peeling of the light-curing acrylic adhesive obtained in Example 7 under the special-shaped structure.
[0143] The applicant believes that this is because the present invention uses dopamine and tetraethyl orthosilicate to compound, add them to ethyl acetate to form an oil phase, form oil-in-water droplets under high-speed stirring, dopamine self-polymerizes to form a small ball structure, and tetraethyl orthosilicate is deposited on its surface. The resulting composite microspheres are calcined to form a porous microsphere structure, and activated on its surface to form activated silica. The resulting activated silica is combined with methacrylic acid and butyl acrylate monomers to obtain methacrylic acid modified silica. Then it is compounded with modified acrylic resin, which not only has good mutual affinity, but also has a very high degree of mutual dispersion uniformity. The microspheres are deformed during the pressing process, so that the system is in full contact with the surface of the adhered workpiece, and has an excellent special-shaped structure bonding effect; and because of the special microsphere structure of the modified silica, it can also play a supporting role between the acrylic adhesive and the adhered workpiece, so that the peeling strength of the acrylic adhesive can be stably maintained, avoiding the occurrence of over-stickiness or non-stickiness, and making it have a good peeling effect. The present invention uses activated graphene as a raw material. Due to the sheet structure of graphene oxide combined with the long carbon chain structure of hexadecyltrimethylammonium bromide bonded thereto, it can not only combine with the monomers that have not yet reacted in the raw material to significantly reduce the thermal shrinkage rate, but also cooperate with the modified silicon dioxide to make the product fit tightly with the special-shaped structure without warping during high temperature, and can also be easily peeled off as a whole under the special-shaped structure, so as to better protect the surface of the workpiece.
[0144] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A light-curing acrylic adhesive for PVD process protection, characterized in that: The raw materials include, by mass: 30-50 parts of modified acrylic resin, 10-30 parts of acrylic monomer, 30-50 parts of modified silicon dioxide, 1-5 parts of free radical initiator, and 1-10 parts of surfactant; The modified acrylic resin is prepared by the following specific steps: hydroxyl-terminated polybutadiene and monohydrogen silicone oil are mixed, heated to 65-75°C and stirred evenly, then a platinum catalyst is added, and the mixture is stirred in a vacuum state for 3.5-4.5 hours to obtain a prepolymer 1; then diphenylmethane diisocyanate is added, and the mixture is stirred in a vacuum state for 40-80 minutes to obtain a prepolymer 2; then 2-hydroxyethyl methacrylate monomer is added, and the mixture is stirred in a vacuum state for 40-80 minutes; The particle size of modified silica is <10 μm; The modified silica is an ultrafine acrylate system modified silica, which is methacrylic acid modified silica; The methacrylic acid modified silica is prepared by the following specific operation: adding nano-silica to deionized water for ultrasonic dispersion for 20-60 minutes, then adding methacrylic acid and an initiator, polymerizing at 80-90° C. for 1-2 hours, cooling to room temperature, vacuum drying, and crushing; Alternatively, methacrylic acid-modified silica is prepared by the following specific operation: adding activated silica, methacrylic acid and butyl acrylate into water and stirring evenly, adding initiator, polymerizing at 80-90° C. for 1-2 hours, cooling to room temperature, vacuum drying and crushing.
2. The light-curing acrylic adhesive for PVD process protection according to claim 1, characterized in that: The molar ratio of hydroxyl-terminated polybutadiene to monohydrogen silicone oil is 3-3.2:1; The sum of the masses of hydroxyl-terminated polybutadiene, monohydrogen silicone oil and platinum catalyst is m , the mass of the platinum catalyst is n ,but n / m =3-5: 1000000.
3. The light-curing acrylic adhesive for PVD process protection according to claim 2, characterized in that: The molar ratio of isocyanate groups in diphenylmethane diisocyanate to hydroxyl groups in prepolymer 1 is 2-2.2:1; The molar ratio of the hydroxyl group in the 2-hydroxyethyl methacrylate monomer to the isocyanate group in the prepolymer is 1-1.1:1; The vacuum degree of the vacuum state is -80 to -100 kPa.
4. The light-curing acrylic adhesive for PVD process protection according to claim 1, characterized in that: The acrylic monomer is at least one of isooctyl acrylate, isodecyl acrylate, isobutyl acrylate, isopropyl acrylate, dodecyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, acryloylmorpholine and isobornyl acrylate.
5. The light-curing acrylic adhesive for PVD process protection according to claim 1, characterized in that: The mass ratio of nano-silicon dioxide, methacrylic acid and initiator is 80-120:2-4:0.01-0.05; Or, the mass ratio of activated silica, methacrylic acid, butyl acrylate and initiator is 5-15:1-3:1-2:0.01-0.1; The initiator is potassium persulfate or sodium persulfate.
6. The light-curing acrylic adhesive for PVD process protection according to claim 1, characterized in that: The activated silica is prepared by the following specific operations: dopamine and tetraethyl orthosilicate are added to ethyl acetate and stirred evenly to obtain a prefabricated material; Tris-HCl solution with a pH value of 8-9 is added dropwise to the prefabricated material at a temperature of 50-60°C and stirred for 1-3 minutes, cooled to 30-36°C, the pH value of the system is adjusted to 6-6.5, stirring is continued for 5-20 minutes, filtered, washed, vacuum dried, and calcined at 500-600°C to obtain porous microspheres, which are then dispersed in an ethanol aqueous solution and stirred evenly, an aminosilane coupling agent is added and ultrasonically treated for 1-2 hours, filtered, and vacuum dried.
7. The light-curing acrylic adhesive for PVD process protection according to claim 1, characterized in that: The raw materials also include: activated graphene, the mass ratio of activated graphene to modified silicon dioxide is 1-3:30-50; The activated graphene is prepared by the following specific operation: adding hexadecyltrimethylammonium bromide and graphene oxide into deionized water, stirring at 50-70° C. for 1-2 hours, filtering, washing, and vacuum drying.
8. A method for preparing a light-curing acrylic adhesive for PVD process protection as claimed in any one of claims 1 to 7, characterized in that: The steps include: a) Stir the modified acrylic resin, acrylic monomer, free radical initiator and surfactant evenly; b) then adding modified silicon dioxide and stirring evenly, or, then adding modified silicon dioxide and activated graphene and stirring evenly; c) After grinding, stir evenly, heat to 68-72℃, adjust the vacuum degree to -80~-100kPa and maintain for 40-80min.
Citation Information
Patent Citations
Adhesive as well as preparation method and application thereof
CN113755126A
Acrylate structural adhesive for polyolefin material bonding and preparation method thereof
CN115895592A